자율신경병증을 동반한 인슐린비의존형 당뇨병환자에서 식도 및 위기능장애에 관한 고찰 - 조재현; Jae Hyun Cho; 강호철; Ho Chul Kang; 선영덕; Young Duk Sun; 양승원; Seung Won Yang; 박철주; Chul Ju Park; 최은진; Eun Jin Choi; et al. (The Korean journal of medicine, 1995)
Objectives: This study was performed to examine the usefulness of the following measurements in evaluating the gastrointestinal motility disturbance in diabetic patients: RGR (Remaining Gastric Radioactivity), GET (Gastric Emptying Time), RER (Remaining Esophageal Radioactivity) and ETT (Esophageal Transit Time) using radianuclide isotope in a liquid diet as well as in a solid diet. Methods: Forty eight non insulin dependent diabetic patients (NIDDM) complaining of gsstrointestinal symptoms were divided into two groups: NlDDM without autonomic neuropathy (Group II, n =21) and NIDDM with autonomic neuropathy (Group III, n=27), and compared with healthy control subjects (Group I, n=51). In each group, ETT, RER, RGR and GET after taking a solid or a liquid diet were measured by the use of radionuclide iso tope. Results: 1) ETT of group III after taking a liquid diet was 24.8±2.76sec, which was significantly longer than those of group I (8.3±0.80sec) and II (8.8±0.48 sec) (p<0.001). 2) ETT of group III after taking a solid diet was 49.20±3.81sec, which was significantly longer than those of group I (18.40±2.32sec) and II (19.75±1.68sec) (p<0.001). 3) RER of group III after taking s liquid diet was 37.2±7.72%, which was significantly higher than those of group I (9.3±0.50) and II (8.3k0.48) (p<0.005). 4) RER of group III after taking a solid diet was 37.84+10.55%, which was significantly higher than those of group I (4.10±0.46%) and II(5.32±0.81 %) (p<0.005). 5) GET of group III after taking a liquid diet was 33.6±2.17min, which was significantly longer than those of group I (21.5±6.70min) and II (26.1±0.40min) (p<0.05). 6) GET of group UI after taking a solid diet was 114.2±8.03min, which was significantly longer than those of group I (61.4±3.65min) and II (60.6±5.21min) (p<0.001). Conclusion: The measurements of ETT as well as GET, using a liquid and a solid diet, are helpful for the evaluations of disorders of esophagogastric motility in patients with diabetic autonomic neuropathy.